Compositional Phases, Geography and Historical Setting behind Judges 4-5 and the Location of Harosheth-ha-goiim. Issue 1 (2nd January 2017) - Finkelstein, Israel
ABSTRACT: In this article I deal with the compositional history, geographical background and possible historical setting of Judges 4-5. I propose that the original heroic, oral material behind these chapters represents two different traditions: One (embedded in Chapter 4) originated in the area of Mount Tabor and the hills to its east and northeast and had the city of Anaharath (the name behind the pun or polemic twist of "Harosheth-ha-goiim") at its core. The other (part of Chapter 5, 19-22) came from the southwestern Jezreel Valley. These traditions represent memories of turbulent 10 th century BCE events—the fall of the last of the late-Canaanite city-states and the take-over of the region by highlanders (Israelites) just before, or in very early days of, the rise of the Northern Kingdom. They were put in writing for the first time by a North Israelite author in the first half of the 8 th century. This author had only vague knowledge of the western valley tradition (Chapter 5); hence while composing the early song, he "imported" details from Chapter 4, merged the two tales into one account, and "expanded" both to portray a broad (North) Israelite scene. A Deuteronomistic author of the late 7 th century BCE inserted the frames characteristic of the Book of Judges, harmonized Chapter 4 with the Jabin story in Joshua 11, included other "explanatory" notes and entered the divine intervention in Chapter 4. A Deuteronomistic author also introduced the adoration of YHWH segments in Chapter 5.